2018
DOI: 10.1111/ijsa.12220
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the validity of structured job interviews with graphical visual aids

Abstract: The structured job interview is often resisted by human resource (HR) professionals despite its superior predictive validity compared to the traditional unstructured interview. However, HR professionals may underestimate the utility of structured interviews because of how validity information is presented. Three online experiments with MTurk samples were conducted to examine the effect of statistical visual aids (Binomial effect size display; expectancy chart; icon array) on people's perceived usefulness of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…Overall, nine studies showed that the effects of different presentation modes of validity information were small and seemed to depend on individual and demographic differences. Furthermore, a complication of using tabular or visual displays to communicate validity evidence in the form of the expected number of successful hires is that a base rate needs to be assumed, which can substantially differ across job selection contexts (50% was assumed in Zhang et al, 2018). The results also suggest that displaying a range of validity coefficients of possible assessment instruments facilitates decision makers' evaluation of validity information.…”
Section: Communication and Presentation Of Scientific Evidencementioning
confidence: 98%
“…Overall, nine studies showed that the effects of different presentation modes of validity information were small and seemed to depend on individual and demographic differences. Furthermore, a complication of using tabular or visual displays to communicate validity evidence in the form of the expected number of successful hires is that a base rate needs to be assumed, which can substantially differ across job selection contexts (50% was assumed in Zhang et al, 2018). The results also suggest that displaying a range of validity coefficients of possible assessment instruments facilitates decision makers' evaluation of validity information.…”
Section: Communication and Presentation Of Scientific Evidencementioning
confidence: 98%
“…Nevertheless, research consistently shows that increasing the use of structured interview could significantly enhance hiring outcomes (Huffcutt & Arthur, 1994;Lubbe & Nitsche, 2019) and reduce adverse impact (Huffcutt & Roth, 1998;Williamson, Campion, & Malos, 1997). Indeed, a bad hire can incur a significant financial cost (Forbes, 2016) have a negative impact on workplace morale and productivity (Dunlop & Lee, 2004) Efforts to combat such resistance have primarily focused on more effective means of presenting statistical evidence (Highhouse et al, 2017;Zhang et al, 2018) or using alternative numerical metrics such as utility analysis (Macan & Highhouse, 1994) to better communicate the value of evidence-based practices to relevant stakeholders. Zhang and colleagues (2018), for example, found that managers were more willing to adopt structured interviews when validity information was presented using alternative graphical displays.…”
Section: Communicating With Storytellingmentioning
confidence: 99%
“…To date, prescriptions for overcoming managers' resistance toward evidence-based hiring practices have primarily focused on more efficient ways to communicate statistical validity evidence (e.g., Highhouse, Brooks, Nesnidol, & Sim, 2017;Zhang, Highhouse, Brooks, & Zhang, 2018). Statistical evidence, however, is not the only tool for persuasion.…”
mentioning
confidence: 99%
“…To date, prescriptions for overcoming managers’ resistance toward evidence‐based hiring practices have primarily focused on more efficient ways to communicate statistical validity evidence (e.g., Highhouse, Brooks, Nesnidol, & Sim, ; Zhang, Highhouse, Brooks, & Zhang, ). Statistical evidence, however, is not the only tool for persuasion.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to combat such resistance have primarily focused on more effective means of presenting statistical evidence (Highhouse et al, ; Zhang et al, ) or using alternative numerical metrics such as utility analysis (Macan & Highhouse, ) to better communicate the value of evidence‐based practices to relevant stakeholders. Zhang and colleagues (), for example, found that managers were more willing to adopt structured interviews when validity information was presented using alternative graphical displays. The persuasive capacity of statistical evidence, however, may be limited: Many managers are not sufficiently trained in statistics or fluent in numerical comprehension (Best, ; Kirsch, Jungeblut, Jenkins, & Kolstad, ).…”
Section: Introductionmentioning
confidence: 99%